Reconfigurable Multi-Three-Phase Propulsion System for Naval Rim-Driven Propeller - Alosa, C.; Immovilli, F.; Lorenzani, E. (2020 International Symposium on Power Electronics, Electrical Drives, Automation and Motion (SPEEDAM), 2020)
Multi-phase drives are the subject of great interest for the transportation electrification. Multi-three-phase machines are used with modular three phase converters to obtain a redundant structure and their great advantage is the fault-tolerance capability. A reconfigurable architecture can be obtained starting from multi-three-phase machine and its characteristic is the possibility to change the winding configuration as a function of the machine speed. This architecture has the advantage of reducing the number of active bridges when the machine operates at low speed, reducing total semiconductors power losses. However, reconfiguration cells are needed to interconnect the windings sets. This cells are usually composed of solid-state bi-directional switches which cause conduction losses. For this reason the analysis of the system losses must be carried out in order to evaluate if the increase in complexity is balanced by an increase in the system efficiency.